A comprehensive comparison between substrate heating and light heating induced nanofluid droplet evaporations. (5th July 2020) - Yan, Xin; Xu, Jinliang; Meng, Zhijun; Xie, Jian
Highlights: Nanofluid droplet evaporations heated by light plasmonic and substrate are studied. Two heating modes behave different flow fields and temperature fields in droplet. Distinct flow fields lead to different nanoparticle patterns for two heating modes. Droplet volume variation has different trends for two heating modes. Surface area decreasing and temperature rise determine the volume variation trend. Abstract: A comprehensive comparison between substrate heating and light plasmonic heating induced nanofluid droplet evaporations is presented. The substrate temperature was kept as 36.5 °C for substrate heating, but a 1400 W/m 2 irradiation flux emitted by a xenon lamp was used for light heating. Both two heating modes yield constant contact diameter evaporation. Because light irradiation reorganizes nanoparticles to generate dynamically varied heat source in nanoscale due to the plasmonic effect, the two heating modes are found to display three differences. First, droplet surface temperature decreases monotonically from contact line to apex for substrate heating, but for light irradiation, droplet surface temperature displays nonmonotonic variation including a contact line region CLR and a bulk volume region BVR. Temperature gradient is significant in CLR but does not exist in BVR. Second, the substrate heating generates both radial flow and Marangoni flow in the whole droplet. Thus, coffee-ring and dispersed nanoparticles are observed on substrate. On the other hand, for light heating, the Marangoni flow is only confined in CLR due to the local temperature gradient there, creating most of nanoparticles deposition near the contact line. Third, because the droplet surface area decreases versus time, the evaporation rate reduces to behave the non-linear variation of droplet volume for substrate heating. The situation is changed for light heating induced droplet evaporation. The enhanced plasmonic heating in CLR due to nanoparticles deposition there offsets the effect of droplet surface area decreasing. Thus, light heating would give rise to the constant droplet evaporation rate, which is distinct to substrate heating. This work enhances the fundamental understanding of the droplet evaporation dynamics under the condition of light heating induced plasmonic heating effect.